Postoperative pain control using continuous i.m. bupivacaine infusion plus patient‐controlled analgesia compared with epidural analgesia after major hepatectomy. Issue 7 (23rd October 2013) - Wong‐Lun‐Hing, Edgar M.; van Dam, Ronald M.; Welsh, Fenella K. S.; Wells, John K. G.; John, Timothy G.; Cresswell, Adrian B.; Dejong, Cornelis H. C.; Rees, Myrddin
Abstract Objectives There is debate concerning the best mode of delivery of analgesia following liver resection, with continuous i.m. infusion of bupivacaine (CIB) plus patient‐controlled i.v. analgesia (PCA) suggested as an alternative to continuous epidural analgesia (CEA). This study compares these two modalities. Methods A total of 498 patients undergoing major hepatectomy between July 2004 and July 2011 were included. Group 1 received CIB + PCA (n = 429) and Group 2 received CEA (n = 69). Groups were analysed on baseline patient and surgical characteristics. Primary endpoints were pain severity scores and total opioid consumption. Secondary endpoints were pain management failures, need for rescue medication, postoperative (opioid‐related) morbidity and hospital length of stay (LoS). Results In both groups pain was well controlled and >70% of patients had no or minimal pain on PoDs 1 and 2. The numbers of patients experiencing severe pain were similar in both groups: PoD 1 at rest: 0.3% in Group 1 and 0% in Group 2 (P = 1.000); PoD 1 on movement: 8% in Group 1 and 2% in Group 2 (P = 0.338); PoD 2 at rest: 0% in Group 1 and 2% in Group 2 (P = 0.126), and PoD 2 on movement: 5% in Group 1 and 5% in Group 2 (P = 1.000). Although the CIB + PCA group required more opioid rescue medication on PoD 0 (53% versus 22%; P < 0.001), they used less opioids on PoDs 0–3 (P ≤ 0.001), had lower morbidity (26% versus 39%; P = 0.018), and a shorter LoS (7 days versus 8 days; P = 0.005). Conclusions The combination of CIB + PCA provides pain control similar to that provided by CEA, but facilitates lower opioid consumption after major hepatectomy. It has the potential to replace epidural analgesia, thereby avoiding the occurrence of rare but serious complications.